Expression–environment associations in transcriptomic heat stress responses for a global plant lineage - Samuel C. Andrew; Anna K. Simonsen; Chris W. Coppin; Pieter A. Arnold; Verónica F. Briceño; Todd G. B. McLay; Chris J. Jackson; Rachael V. Gallagher; Karel Mokany (Molecular Ecology, 2024)
The increasing frequency and severity of heatwaves will intensify stress on plants. Given regional variation in heatwave exposure and expected differences in thermal tolerance between species it is unlikely that all plant species will be affected equally by climate change. However, little is currently known about variation in the responses of plants to heat stress, or how those responses differ among closely related species adapted to different environments. Here we quantify the response of 17 Acacia species (175 RNA‐seq libraries), from across Australia's diverse biomes, to a multi‐day experimental heatwave treatment to identify variation in transcriptomic and physiological responses to heat stress. Genes with known heat response functions showed consistent responses across Acacia species. Up to 10% of all genes and over 100 gene families showed significant clinal variation in the magnitude of their expression plasticity across species. Specifically, gene families linked to the temperature stress response were overrepresented among significant relationships with home range temperature conditions. Gene expression responses seen on the first day of the heatwave were more frequently associated with home range climates, while expression responses by day four were more commonly related to photosystem II acclimation. Comparative transcriptomics on non‐model species has the potential to provide key information on stress response plasticity, especially when linked with our understanding of model species. Our study indicates that the pressing challenge to identifying potentially vulnerable species to climate change could be benefited by the further exploration of clinal variation in transcriptome plasticity.

Long-term exposure to traffic noise and risk of incident colon cancer: A pooled study of eleven Nordic cohorts - Nina Roswall; Jesse D. Thacher; Mikael Ögren; Andrei Pyko; Agneta Åkesson; Anna Oudin; Anne Tjønneland; Annika Rosengren; Aslak H. Poulsen; Charlotta Eriksson; David Segersson; Debora Rizzuto; et al. (Environmental Research, 2023)

Novel model‐based clustering reveals ecologically differentiated bacterial genomes across a large climate gradient - Anna K. Simonsen; Luke G. Barrett; Peter H. Thrall; Suzanne M. Prober (Ecology Letters, 2019)
A pervasive challenge in microbial ecology is understanding the genetic level where ecological units can be differentiated. Ecological differentiation often occurs at fine genomic levels, yet it is unclear how to utilise ecological information to define ecotypes given the breadth of environmental variation among microbial taxa. Here, we present an analytical framework that infers clusters along genome‐based microbial phylogenies according to shared environmental responses. The advantage of our approach is the ability to identify genomic clusters that best fit complex environmental information whilst characterising cluster niches through model predictions. We apply our method to determine climate‐associated ecotypes in populations of nitrogen‐fixing symbionts using whole genomes, explicitly sampled to detect climate differentiation across a heterogeneous landscape. Although soil and plant host characteristics strongly influence distribution patterns of inferred ecotypes, our flexible statistical method enabled us to identify climate‐associated genomic clusters using environmental data, providing solid support for ecological specialisation in soil symbionts.

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Leaf shape variation and herbivore consumption and performance: a case study with Ipomoea hederacea and three generalists - Brandon E. Campitelli; Anna K. Simonsen; Andrea Rico Wolf; Jessamyn S. Manson; John R. Stinchcombe (Arthropod-Plant Interactions, 2008)

Induced responses in Ipomoea hederacea: simulated mammalian herbivory induces resistance and susceptibility to insect herbivores - Anna K. Simonsen; John R. Stinchcombe (Arthropod-Plant Interactions, 2007)